2019
DOI: 10.1038/s41598-019-54783-x
|View full text |Cite
|
Sign up to set email alerts
|

2-D Peripheral image quality metrics with different types of multifocal contact lenses

Abstract: To evaluate the impact of multifocal contact lens wear on the image quality metrics across the visual field in the context of eye growth and myopia control. Two-dimensional cross-correlation coefficients were estimated by comparing a reference image against the computed retinal images for every location. Retinal images were simulated based on the measured optical aberrations of the naked eye and a set of multifocal contact lenses (centre-near and centre-distance designs), and images were spatially filtered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…There is a decreasing range of defocus for eye compensation from mice, avian, to primate; thus, we assume that humans may have a narrow range of defocus power where eye growth can be manipulated. Garcia et al [36] reported in a study that superimposing myopic defocus for compensating hyperopic RPR in myopes, in some cases, could degrade the peripheral image quality. DIMS lens wearers with baseline myopic RPR received too much myopic defocus at the mid-periphery retina, which can result in an overall peripheral image blur beyond the threshold of signal detection, and myopia control would therefore be less effective [37,38].…”
Section: The Effective Range Of Myopic Defocus In Myopia Controlmentioning
confidence: 99%
“…There is a decreasing range of defocus for eye compensation from mice, avian, to primate; thus, we assume that humans may have a narrow range of defocus power where eye growth can be manipulated. Garcia et al [36] reported in a study that superimposing myopic defocus for compensating hyperopic RPR in myopes, in some cases, could degrade the peripheral image quality. DIMS lens wearers with baseline myopic RPR received too much myopic defocus at the mid-periphery retina, which can result in an overall peripheral image blur beyond the threshold of signal detection, and myopia control would therefore be less effective [37,38].…”
Section: The Effective Range Of Myopic Defocus In Myopia Controlmentioning
confidence: 99%